The Leptomeninges Produce Prostaglandin D2 Involved in Sleep Regulation in Mice - Cherasse, Yoan; Aritake, Kosuke; Oishi, Yo; Kaushik, Mahesh K.; Korkutata, Mustafa; Urade, Yoshihiro (Frontiers in Cellular Neuroscience, 2018)
Injection of nanomolar amounts of prostaglandin D2 (PGD2) into the rat brain has dose and time-dependent somnogenic effects, and the PGD2-induced sleep is indistinguishable from physiologic sleep. Sleep-inducing PGD2 is produced in the brain by lipocalin-type PGD2 synthase (LPGDS). Three potential intracranial sources of LPGDS to produce PGD2 have been identified: oligodendrocytes (OD), choroid plexus (CP), and leptomeninges (LM). We aimed at the identification of the site of synthesis of somnogenic PGD2 and therefore, generated a transgenic mouse line with the LPGDS gene amenable to conditional deletion using Cre recombinase (flox-LPGDS mouse). To identify the cell-type responsible for producing somnogenic PGD2, we engineered animals lacking LPGDS expression specifically in the oligodendrocytes (OD-LPGDS KO), choroid plexus (CP-LPGDS KO), or leptomeninges (LM-LPGDS KO). We measured prostaglandins and LPGDS concentrations together with PGD synthases (PGDS) activity in the brain of these mice. While the LPGDS amount and PGD synthase activity were drastically reduced in the OD- and LM-LPGDS KO mice, they were unchanged in the CP-LPGDS KO mice compared with control animals. We then recorded electroencephalograms, electromyograms, and locomotor activity to measure sleep in 10-week-old animals with specific knockdown of LPGDS in each of the three targets. Using selenium tetrachloride, a specific PGDS inhibitor, we demonstrated that sleep was inhibited in OD-LPGDS and CP-LPGDS KO mice, but not in the LM-LPGDS KO mice. We concluded that somnogenic PGD2 is produced primarily by the leptomeninges, and not the oligodendrocytes or choroid plexus.